Implementasi Program Urban Farming pada Kelompok Tani Subur Kedurus Kota Surabaya - Muhammad Aulia Yahya; Diana Hertati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This study aims to determine the implementation model of the urban farming program in improving the agricultural sector in the city of Surabaya along with. To find out, a descriptive-qualitative research type was used, with data collection techniques of interviews, observation, and documentation. The results of the study show that there are similarities between the models for implementing the urban farming program for the three elements, including the urban farming program, the Food and Agriculture Security Service, and the Subur Kedurus Farmers Group which are both interrelated and influence the successful implementation of the program. In the implementation of the urban farming program at the Subur Kedurus Farmer Group it is in accordance with the policies made by the Surabaya City government, seen from the existence of community participation and public awareness in the form of mutual cooperation, labor, to the existence of vacant private land to be used for urban farming and there are suggestions from community especially farmer groups for fertilizer subsidies and directions in marketing products to improve the community's economy. However, there are still obstacles, namely the lack of absorption of fertilizer which results in a decrease in the amount of harvest